Lipoprotein particles exhibit distinct mechanical properties. Issue 12 (18th December 2022) - Piontek, Melissa C.; Roos, Wouter H.
Abstract: Lipoproteins (LPs) are micelle‐like structures with a similar size to extracellular vesicles (EVs) and are therefore often co‐isolated, as intensively discussed within the EV community. LPs from human blood plasma are of particular interest as they are responsible for the deposition of cholesterol ester and other fats in the artery, causing lesions, and eventually atherosclerosis. Plasma lipoproteins can be divided according to their size, density and composition into chylomicrons (CM), very‐low‐density lipoproteins (VLDL), low‐density lipoproteins (LDL) and high‐density lipoproteins (HDL). Here, we use atomic force microscopy for mechanical characterization of LPs. We show that the nanoindentation approach used for EV analysis can also be used to characterize LPs, revealing specific differences between some of the particles. Comparing LPs with each other, LDL exhibit a higher bending modulus as compared to CM and VLDL, which is likely related to differences in cholesterol and apolipoproteins. Furthermore, CM typically collapse on the surface after indentation and HDL exhibit a very low height after surface adhesion both being indications for the presence of LPs in an EV sample. Our analysis provides new systematic insights into the mechanical characteristics of LPs.